TV OPERA-DASTAN “BUKHOROI SHARIF” (“HOLY BUKHARA”) MUSTAFO BAFOYEV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the teleopera-dastan «Bukhoroi Sharif» by the Honored Artist of Uzbekistan, laureate of the State Prize named after Abdulla Kadiri, world-famous composer, conductor, professor of the State Conservatory of Uzbekistan Mustafa Bafoev, intended for a large orchestra of Uzbek folk instruments, piano, reader, soloists and mixed choir. The author of the article, a leading specialist in the field of folk instrumental culture of Uzbekistan, Doctor of Arts, professor of the State Conservatory of Uzbekistan reveals the ideological and artistic epic essence of the teleopera-dastan, analyzes the functions and performance techniques of musical instruments in the embodiment of the historical images of the main characters, the musical dramaturgy of the work. In the development of this topic, such methods of scientific research as historical-analytical, comparative, axiological, complex are used. The practical result of the scientific research is that a monumental heroic-epic work has been created, which has a highly artistic value in the formation of the young generation in the spirit of patriotism, the continuity of national traditions in the perception of the genre of teleopera as an effective means of mass communication. This work develops one of the main lines of the composer’s creativity, associated with reliable images of the historical past, sights that have preserved and brought to our time the memory of centuries, colorful pictures of the sacred city of Bukhara, which received new meanings and significance in the musical art of the era of globalization.
Keywords: Mustafo Bafoev, teleopera-dastan «Bukhoroi Sharif» («Sacred Bukhara»), orchestra of Uzbek folk instruments, bakhshi, youth, spiritual world.